2009
DOI: 10.1016/j.jasms.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Metal imaging on surface of micro- and nanoelectronic devices by laser ablation inductively coupled plasma mass spectrometry and possibility to measure at nanometer range

Abstract: An analytical mass spectrometric method for the elemental analysis of nano-bioelectronic devices involved in bioengineering research was developed and applied for measurements of selected metals (Au, Ti, Pt, Cr, etc.) on interdigitated electrode array chips (IDA-chip). An imaging laser ablation inductively coupled plasma mass spectrometric (LA-ICP-MS) procedure was used to map the elements of interest on the surface of the analyzed sample. The obtained images of metals were in a good agreement and corresponded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Using a large laser ablation chamber, commercially available from CETAC Technologies, the Cu and Zn distribution in a 20-mm tissue section of human brain hemisphere (110 mm  65 mm) was analyzed. In contrast, small laser ablation cells for development of Nano-LA-ICP-MS using near field effect at the nm spatial resolution were devised for future application in clinical studies on single cells by Becker and coworkers [61,63,64].…”
Section: Generalmentioning
confidence: 99%
See 3 more Smart Citations
“…Using a large laser ablation chamber, commercially available from CETAC Technologies, the Cu and Zn distribution in a 20-mm tissue section of human brain hemisphere (110 mm  65 mm) was analyzed. In contrast, small laser ablation cells for development of Nano-LA-ICP-MS using near field effect at the nm spatial resolution were devised for future application in clinical studies on single cells by Becker and coworkers [61,63,64].…”
Section: Generalmentioning
confidence: 99%
“…The spot size of the laser beams varied between 50 and 200 mm, and the laser power density from 1 to 3 Â 10 9 W cm À2 . Ion intensities of the analytes, for example, of 64 Zn þ , were measured by LA-ICP-MS within the area of interest in different regions of the human brain tissue (e.g., human hippocampus) [38].…”
Section: Bioimaging Of Metals and Quantification Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 In singleshot measurements by NF-LA-ICP-MS, it is demonstrated that significantly enhanced ion intensity of the laser-ablated materials was monitored by double focusing sector field ICP-MS when the thin Ag needle tip was close to the sample surface due to the nearfield enhancement. [9][10][11][12] Recently, a three-dimensional movement piezo has been introduced under the sample holder to permit imaging of samples by the novel NF-LA-ICP-MS. In addition, the system for controlling the 'tip-to-sample' distance has been adapted with a dynamic non-contact feedback mode, which makes it possible to analyze biological samples.…”
Section: -5mentioning
confidence: 99%